JR Mr: HUBUNGAN KUALITAS PEMBELAJARAN DAN MINAT BELAJAR DARING DENGAN HASIL BELAJAR PJOK SELAMA PANDEMI COVID-19 - Joan Rhobi Andrianto; Yully Wahyu Sulistiyo (Universitas Majalengka, 2022)
Several factors that can affect learning outcomes are the quality of learning and interest in learning. During the Covid-19 pandemic, the teaching and learning system underwent changes, namely there was no face-to-face learning or so-called learning from home and online learning was implemented. It is known from interviews with classroom teachers that interest in learning and learning outcomes are low. The objectives of this study are: (1) to determine the relationship between quality and learning outcomes during the Covid-19 pandemic, (2) to determine interest in online learning and learning outcomes during the pandemic, (3) to determine the relationship between quality and interest in online learning and learning outcomes. learn students during the pandemic.This research method is correlation research. The population of this study amounted to 285 students. The research sample amounted to a sample of 156 students by means of cluster random sampling. Data collection methods in this study used interviews, documentation and questionnaires. The research analysis technique uses person correlation and multiple correlation. The results of this study show: (1) there is no relationship between the quality of learning and learning outcomes during the Covid-19 pandemic with an rcount of -0.148 < rtable 0.1572 a significant value of 0.06 > 0.05, (2) there is no relationship between interest in learning online learning outcomes during the Covid-19 pandemic with an rcount value of 0.107 < rtable 0.1572 a significant value of 0.184 > 0.05, (3) there is no relationship between quality and interest in online learning with student learning outcomes during the Covid-19 pandemic with an rcount value -0.145 <rtable0.1572 significant value of 0.92 > 0.05. The conclusion of this study shows that there is no relationship between learning quality and online learning interest with student learning outcomes during the Covid-19 pandemic.